For a quadratic equation, ax2 + bx + c = 0,
D = b2 – 4ac
If D = 0, roots are equal
⇒ D = 4m2c2 – 4(c2 – a2)(1 + m2) = 0
⇒ m2c2 – c2 + a2 – c2m2 + a2m2 = 0
⇒ c2 = a2(1 + m2)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation